2023
DOI: 10.1227/neu.0000000000002483
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Transforaminal Lumbar Interbody Fusion in the Ambulatory Surgery Center Versus Inpatient Setting: A 1-Year Comparative Effectiveness Analysis

Abstract: BACKGROUND: Ambulatory surgery centers (ASCs) have emerged as an alternative setting for surgical care as part of the national effort to lower health care costs. The literature regarding the safety of minimally invasive transforaminal lumbar interbody fusion (MIS TLIF) in the ASC setting is limited to few small case series. OBJECTIVE: To assess the safety and efficacy of MIS TLIF performed in the ASC vs inpatient hospital setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…In our review, only six studies compared PROMs between inpatient and outpatient fusion groups, most often reporting VAS Back, VAS Leg, and ODI. 19,23,26,27,30,31 Qualitatively, all six studies reported no difference between IPS and OPS cohorts for VAS Back, five of which similarly reported no difference for VAS Leg. 23,26,27,30,31 Only Nie et al reported a significant difference between groups for VAS Leg at one year , with the OPS cohort having a lower VAS Leg at this time point.…”
Section: Patient-reported Outcomesmentioning
confidence: 89%
See 4 more Smart Citations
“…In our review, only six studies compared PROMs between inpatient and outpatient fusion groups, most often reporting VAS Back, VAS Leg, and ODI. 19,23,26,27,30,31 Qualitatively, all six studies reported no difference between IPS and OPS cohorts for VAS Back, five of which similarly reported no difference for VAS Leg. 23,26,27,30,31 Only Nie et al reported a significant difference between groups for VAS Leg at one year , with the OPS cohort having a lower VAS Leg at this time point.…”
Section: Patient-reported Outcomesmentioning
confidence: 89%
“…19,23,26,27,30,31 Qualitatively, all six studies reported no difference between IPS and OPS cohorts for VAS Back, five of which similarly reported no difference for VAS Leg. 23,26,27,30,31 Only Nie et al reported a significant difference between groups for VAS Leg at one year , with the OPS cohort having a lower VAS Leg at this time point. 19 Two 26,31 of the four 19,26,27,31 studies that reported ODI found a significant improvement for OPS compared with IPS.…”
Section: Patient-reported Outcomesmentioning
confidence: 89%
See 3 more Smart Citations